2021
DOI: 10.1038/s41467-021-21462-3
|View full text |Cite
|
Sign up to set email alerts
|

Stable single atomic silver wires assembling into a circuitry-connectable nanoarray

Abstract: Atomic metal wires have great promise for practical applications in devices due to their unique electronic properties. Unfortunately, such atomic wires are extremely unstable. Here we fabricate stable atomic silver wires (ASWs) with appreciably unoccupied states inside the parallel tunnels of α-MnO2 nanorods. These unoccupied Ag 4d orbitals strengthen the Ag–Ag bonds, greatly enhancing the stability of ASWs while the presence of delocalized 5s electrons makes the ASWs conducting. These stable ASWs form a coher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…Under the strong coordinative interaction of the CN x site with the Pd atoms, the gradual transformation of the Pd-NPs into single atoms at high temperature was observed 17 . The reverse sintering transformation from nanoparticles to single atoms was also confirmed in the systems of silver particles supported on Hollandite-type manganese oxide and Pt particles loaded on Fe 2 O 3 19 21 . DFT calculations suggested that the reverse sintering effect requires the coordination of the metal-support bond significantly exceeded the internal metal-metal binding inside the particles, leading to a thermodynamically favorable redispersion of metal particles to the most stable single atomic dispersion geometry.…”
Section: Introductionmentioning
confidence: 54%
“…Under the strong coordinative interaction of the CN x site with the Pd atoms, the gradual transformation of the Pd-NPs into single atoms at high temperature was observed 17 . The reverse sintering transformation from nanoparticles to single atoms was also confirmed in the systems of silver particles supported on Hollandite-type manganese oxide and Pt particles loaded on Fe 2 O 3 19 21 . DFT calculations suggested that the reverse sintering effect requires the coordination of the metal-support bond significantly exceeded the internal metal-metal binding inside the particles, leading to a thermodynamically favorable redispersion of metal particles to the most stable single atomic dispersion geometry.…”
Section: Introductionmentioning
confidence: 54%
“…Furthermore, in analogy with the self-assembly of multidimensional materials at the nano level, self-assembly of atoms at the single-atom level might be promising. For example, single-atom chains show potential application in either catalysis or quantum computation, but so far they were only obtained on the single crystal surfaces or inside the tunnels of oxide . Hopefully the fabrication of single-atom chains by self-assembly will be flourishing in the near future.…”
mentioning
confidence: 99%
“…Under the strong coordinative interaction of the CN x site with the Pd atoms, the gradual transformation of the Pd-NPs into single atoms at high temperature was observed 16 . The reverse sintering transformation from nanoparticles to single atoms was also con rmed in the systems of silver particles supported on Hollandite-type manganese oxide and Pt particles loaded on Fe 2 O 3 [18][19][20] .…”
Section: Introductionmentioning
confidence: 94%